AUGMENTED REALITY IN COLOMBIAN BASIC EDUCATION: AN IN-DEPTH ANALYSIS OF ITS PEDAGOGICAL AND TECHNOLOGICAL IMPLICATIONS - Karina Tarazona Romero (LÍNEA IMAGINARIA, 2025)
Nowadays, technologies have largely taken over the processes that involve society, so one of the scenarios that has had a high impact is education, where it is possible to see that new strategies and contents that point to ways of teaching and learning arise daily, where artificial intelligences have reached a good role and that is why the present general objective arises: to reflect on the theoretical foundation of augmented reality in Colombian basic education; for a deep analysis of its pedagogical and technological implications. The methodology used focuses on a documentary analysis that leads to generate an academic essay, whose results indicate that augmented reality is conceived as a process that superimposes digital information creating interactive experiences that point to the management of conceptual elements in the virtual environment. From this point of view, it is pertinent to take into account that it was concluded that augmented reality allows the adaptation of content according to the topics that are being addressed, thus establishing resources and strategies that converge in what is a successful teaching process that leads to give a special plus in the theoretical and procedural construction of comprehensive teaching models that contribute to familiarize students with the environment, in such a way that they are impregnated with technological advances and are able to penetrate with an effective teaching model.